2020
DOI: 10.21009/141.10
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Disaster Management Media Through Picture Story Books

Abstract: Indonesia is a country that has a high potential for natural disasters. Picture story book is a form of disaster management learning that can help children from an early age to prepare for a natural disaster. The aims of this study to develop story books as a disaster management learning media, to improve knowledge and skills of children and teacher about the understanding, principles, and actions of rescue when facing the natural disasters, to increase the teacher’s learning quality in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…The systematic literature review identified nine manuscripts. Four of these described books focused on natural disasters including typhoons, hurricanes and storms ( Sharpe and Izadkhah, 2014 ; Marvida and Tibayan, 2019 ; McKeon, 2020 ; Solfiah et al ., 2020 ), and five related to health messaging including sun safety and juvenile idiopathic arthritis ( Thornton and Piacquadio, 1996 ; McDermott and Lowe, 2003 ; Armstrong, 2012 ; Egert et al ., 2017 ; Robinson et al , 2017 ). None of the identified manuscripts described the development of books for children relating specifically to bushfires or bushfire smoke.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic literature review identified nine manuscripts. Four of these described books focused on natural disasters including typhoons, hurricanes and storms ( Sharpe and Izadkhah, 2014 ; Marvida and Tibayan, 2019 ; McKeon, 2020 ; Solfiah et al ., 2020 ), and five related to health messaging including sun safety and juvenile idiopathic arthritis ( Thornton and Piacquadio, 1996 ; McDermott and Lowe, 2003 ; Armstrong, 2012 ; Egert et al ., 2017 ; Robinson et al , 2017 ). None of the identified manuscripts described the development of books for children relating specifically to bushfires or bushfire smoke.…”
Section: Resultsmentioning
confidence: 99%
“…All manuscripts indicated their primary target audience was children, with age ranges of 2–3 years (as in McDermott and Lowe, 2003 ), 2–6 years (as in Robinson et al ., 2017 ), 5–6 years (as in Solfiah et al ., 2020 ), 5–8 years (as in Armstrong, 2012 ), 8–9 years (as in Thornton and Piacquadio, 1996 ), and the remainder not specifying a specific age range ( Egert et al , 2017 ; Marvida and Tibayan, 2019 ; McKeon, 2020 ). Most authors interviewed who discussed the target age group noted the age ranges of their works were typically dictated by their publisher.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings demonstrate that children and teachers alike respond well to Pop-Up Book media items. Another study conducted by Solfiah et al, (2020) on the development of picture storybooks found that children's understanding about disaster management was 47.92 percent on average before the exam, but improved to 76.88 percent after the test. This suggests that picture-book medium can be effectively used to raise public awareness of disaster management.…”
Section: Book As Learning Mediamentioning
confidence: 99%